Pedagogy as enchantment: teaching and learning processes as cure for the necessary revolutions (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This manuscript aims to act as a spell in the search for the cure for what could be named as colonial disease. It supports the adoption of the term pedagogy as enchantment in order to conceive the teaching and learning processes as a way of intervening in the world and change the objective reality of humans. Therefore,pedagogy could be considered as a kind of everyday magic. The manuscript also reflects upon how such recognition can echo in performance practices, reaching the understanding that it may transform the methodologies that already exist, and create other ones, as long as those methodologies consider some aspects: the reliance in the creative ability/capacity of others, an action that guides their practice and the conception that the world can be transformed.
Keywords: Pedagogy; Cure; Theate; Teaching-learning processes; Intervention